Tissue evidence of the testosterone role on the abnormal growth and aging effects reversion in the gerbil (Meriones unguiculatus) prostate - Scarano, Wellerson Rodrigo (2006)
Prostate differentiation during embryogenesis and its further homeostatic state maintenance during adult life depend on androgens. Abundant biological data suggest that androgens play an important role in the development of the prostate cancer and other prostatic diseases. The objective of this work was to evaluate the effects of the testosterone supplementation in gerbil (a new experimental model) at different ages. Tissues from experimental animals were studied by histological and histochemistry procedures, androgen receptor immunohistochemistry assay, morphometric-stereological analysis, and transmission electron microscopy (TEM). After the treatment were observed increase of prostate weight and epithelium height in all ages studied. In some adult and aged treated animals, hyperplasic and displasic process were observed, including prostatic intraepithelial neoplasias and adenocarcinomas. Increase of the thickness of the smooth muscle cell (SMC) layer was observed in pubescent and adult animals and TEM revealed apparent SMC hypertrophy. An apparent increase in the frequency of blood vessels distributed by the subepithelial stroma in the treated animals was noticed. Reversion of the natural effects of aging on the prostate was observed in the aged treated animals in some acini of the gland. These data demonstrate that the gerbil prostate is susceptible to androgenic action at the studied ages and it can serve, for example, as experimental model to studies of prostate neoplasic process induction and hormonal therapy in aged animals.